APLIKASI PENDEKATAN THEORY OF REASONED ACTION UNTUK MEMPERIKSI MINAT MASUK MENJADI PESERTA MANDIRI BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN (Studi Kasus: Masyarakat Kecamatan Medan Selayang) - Saragih, Nawary (Jurnal Manajemen dan Bisnis, 2017)
In BPJS Health still happened paradox rights, that is for health protection there is still ambiguity happened at Mitra Hospital which not as expected with that felt by patient, for example for certain sick like cancer for chemo process only long and difficult service for certain reasons as well. This is contrary to expectations by the Minister of Health proposed by Nafsiah Mboi that BPJS Health will endeavor to bear all kinds of diseases. Based on this, the research problem is formulated "Whether the theory of reasoned action can be used to predict the interest of the community to be a Mandiri BPJS Health participant in Medan Selayang Society". The purpose of this study is to determine the application of the theory of reasoned action in predicting the interest of entering into a participant Mandiri BPJS Health. While the benefit of the research is to provide information to the management of BPJS Health about the theory of reasoned action to predict the interest to be a participant Mandiri BPJS Health. Determination of the sample is done incidentally ie kusioner given to the Society which when met with researchers in the research location. The number of samples is determined based on the maximum error (sampling error). From the research results can be concluded that: (a). Attitudes and preference groups to be participants of Independent BPJS Health on average respondents give a positive effect (strong) on the intention to behave. (b). Based on the equation of intention to enter the participants into the Mandiri BPJS Health as a requirement of 0.62 (62%). While the effect on subjective Norm (SN) is 0.38 (38%). As a consideration (a). BPJS Health Management needs to improve the consistency of services for the required attribute benefits in accordance with the demands of positive participants on the presence of BPJS Health, (b). BPJS Health Management continuously needs to learn the attitudes of participants, because this can be used as a basis to increase the number of participants and improve the satisfaction of a prosperous Society.